The effects of work ethics on work attitude the case of Coca-Cola Bottler's Philippines, Inc. (CCBPI) Ungka, Pavia, Iloilo - Correos, Rey Kenneth Isaac; Fabila, Jose Angelo; Fajutar, Julie (2005.)
This study focuses on finding out the effects of work ethics on work attitudes of the employees. The independent variable of this study is work ethics and the dependent variable is attitude towards work. Indicators for each variable were also identified for work ethics the indicators are initiative, honesty, trustworthiness, sense fairness, and ensuring safety in the work place. For attitude towards work the indicators are attendance, productivity, and teamwork. The study used thee descriptive research design to explain clearly the results gathered by the researchers. Survey questions were formulated and were used to gather the information needed for the study. The questionnaires were distributed to fifteen employees who were randomly chosen from the different departments of CCBPI to become the respondents of the study. After the survey was computed. After computing the results it was then interpreted and analyzed. The result of the study shows that the CCBPI employees have strong work ethics wherein they give high regard with the morals and work values of individuals in the company. The researchers conclude also that work ethics greatly affects the attitudes towards work of CCBPI employees. Work ethics such as initiative, honesty, trustworthiness, sense of fairness, and ensuring safety in the work place affects the attitude towards work of the employee such as attendance, productivity, and teamwork. Furthermore, CCPBI does not only focus on the quantity and quality of their product but also to the quality of the person responsible for producing it. The company does not only pay high regard with the technical and conceptual skills of their employees but also with the attitudes of their employees.
Research Paper (Mgt 199-Management Research). -- Iloilo City : University of the Philippines in the Visayas - College of Management, October 2005.